IDENTIFICATION OF HOSPITAL BUILDING CHANGES AS EVIDENCE-BASED DESIGN PROCESS - Indrawan, Iwan Adi; Faqih, Muhammad; Purnomo, Hari (Border: Jurnal Arsitektur, 2019)
Nowadays evidence-based design in the hospital design process is increasingly needed in making design decisions. This process provides an opportunity for architects to be able to find new solutions in anticipating various problems related to architectural aspects. One of the problems that exist in the hospital building types is the need to accommodate change. The change referred to in this case is a change in the architecture of the building's configuration. The existence of change requires a flexible and adaptive architectural design. Change provides an opportunity to grow and improve but also provides chance for problems. In this case the problem faced is the tendency of the need for spatial changes both due to their capacity and function. the research aims to identify the form of change as an initial step in the design stage. The method used is a literature study and case study at a public hospital in Surabaya to determine the trends in the form of changes that generally occur. Based on the results obtained there are five types of changes, namely Volume, service lines, Patient mix and standard of care, Size and Medical Discovery, and three types of changes that can occur in hospital architecture, namely improvisation, Building changes, Expansion Building (Building Extension). The trends in the types and forms of change in the two hospitals are Volume and improvisation.